GREEN INNOVATION DAN WASTE MANAGEMENT: FAKTOR KUNCI BUSINESS SUSTAINABILITY UMKM - Muhammad Fikri Arrafi; Ira Hapsari; Rezky Pramurindra; Iwan Fakhruddin; Edi Joko Setyadi (JURNAL ILMIAH EDUNOMIKA, 2026)
MSME’s are a sector that plays a crucial role in the national economy. However, the sustainability of their businesses is often hindered by the lack of adoption of environmentally friendly practices. This study aims to analyze the influence of green innovation and waste management on business sustainability among MSME’s. Data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach, including both outer and inner model testing. The population of this research consists of all Micro, Small, and Medium Enterprises in Banyumas Regency. A stratified random sampling technique was employed to obtain respondents that met the predetermined criteria, and primary data were collected through questionnaires. The findings reveal that: (1) green innovation has a positive effect on business sustainability; and (2) waste management has a positive effect on business sustainability.